(untitled) (Conference on English Language Teaching, 2025)
This study investigates the advantages of using Discord to enhance the speaking skills of UIN SAIZU students. Discord is a versatile communication platform initially popular among gamers, is increasingly utilized in educational contexts due to its accessibility, real-time interaction features, and user-friendly design. This qualitative research employed structured interviews with five UIN SAIZU students who actively use Discord for communication and language practice. Findings reveal that Discord fosters confidence, reduces speaking anxiety, and encourages frequent practice through engaging features such as voice channels and anonymity options. Students highlighted the platform’s ability to connect them with international peers, facilitating meaningful conversations that improve fluency and vocabulary. The ease of access and user-friendly interface also encouraged students to recommend the platform to others. Even casual use for gaming contributed to daily speaking practice. Furthermore, unique features like anonymity, which allows for open communication without revealing personal identity, and interesting servers, support regular speaking practice. Despite its effectiveness, the study identifies the need for structured activities and further analysis of its long-term impact on speaking skills. Overall, this research demonstrates Discord’s potential as a practical tool for enhancing language proficiency in educational settings, offering an engaging and accessible environment for speaking skill development.